O estado da Arte das pesquisas brasileiras sobre geometria analítica no período de 1991 a 2014 - Santos, Adriana Tiago Castro dos (2016)
This study aims to present the "State of the Art" of Brazilian researches in the period 1991-2014 on the teaching and learning of Analytic Geometry in Brazil. We have adopted the assumptions of Content Analysis to carry out the methodological procedures and we have used the theoretical ideas of Dreyfus (1991) on which the processes of Advanced Mathematical Thinking (AMT) have emerged implicitly from pedagogical approaches addressed in academic productions for data analysis. Data were collected through bibliographic survey in theses and dissertations in the thesis database of CAPES and through sites from Strictu Sensu Graduate Programs in Mathematics Education in Brazil. We have identified forty-one academic productions about teaching and learning Analytical Geometry. We created two axes of analysis: the academic productions that used ICTs as a research subject and the academic productions that have not used ICTs as a primary focus. In researches using ICT as a research focus, the authors have used dynamic geometry software, spreadsheets and Moodle platform as a tool for teaching Analytic Geometry. In academic productions that did not target ICTs as focus, we have used tools such as compass and ruler for the construction of geometric entities, manipulative materials and techniques of isometric perspective, construction of geometric figures in 3D for the resolution of problem situations and the diversification among the semiotic representation registers. We detected that AMTs processes such as visualization, change of representation and abstraction were implicit in the activities proposed by these academic productions. We have concluded that the themes of analytic geometry covered in the research have not changed over the period considered. What have changed were the teaching and learning strategies that are centered on the student now, thus allowing him to create a more active role in the learning process without relying strictly on the teacher